Students' responses to the use of authentic materials in ESL listerning lessons : the case ofupper six form students in SMK Batu Lintang, Kuching - Helena Bulan, Apoi (University Malaysia Sarawak, UNIMAS, 2005)
In the last twenty years, the use of authentic listening materials has become common in ESL classroom teaching that the aim is to increase the students' interest in the lesson, participation in the task, enjoyment in the lesson and persistence with the task throughout the whole lesson. In this study, the aim is to investigate the students responses to the use of authentic listening materials in ESL listening lessons in terms of their interest in the lesson, persistence to the learning task, enjoyment and participation in the learning task. The data was collected over a two-week observation (ten times on ten different days) for a thirty minute listening lesson. This involved 40 Upper Six form students at SMK Batu Lintang. The class used authentic materials and non-authentic materials. The data was collected on alternate days when the students were performing the tasks related to the listening materials. The findings suggest to some extent, students reported authentic listening materials such as the song to be significantly more interesting, exciting, absorbing and increase their enjoyment, persistence to the learning task and participation in the learning task among the other listening materials. However, the overall finding revealed that the students' interest in the lesson, persistence to the learning task, enjoyment and participation in the learning task increased significantly when nonauthentic listening materials were used compared to the other authentic listening materials such as the news broadcast, the telephone conversation, the interview and the announcements.